Benefits of a symbiotic association with endophytic fungi are subject to water and nutrient availability in Achnatherum sibiricum - Ren, An Zhi; Li, Xia; Han, Rong; Yin, Li Jia; Wei, Mao Ying; Gao, Yu Bao (Plant and soil, 2011)
Symbiotic relationships with microbes may influence how plants respond to environmental change. Here, we investigated how fungal endophyte infection affected the growth of a native grass under altered water and nutrient availability. In a two-month field experiment, we compared the performance of endophyte-infected (EI) and endophyte-free (EF) Achnatherum sibiricum subjected to four treatments comprised of a factorial combination of two levels of water availability and two levels of fertilization. The greatest benefits of endophyte infection occurred in the well-watered fertilized treatment. With reduced water and/or nutrient availability, the benefits declined. EI plants subjected to drought and fertilization had higher root:shoot ratios and allocated more nitrogen to photosynthetic machinery and thus had a higher net photosynthetic rate than EF counterparts. In the well-watered unfertilized treatment, EF plants allocated more nutrients to photosynthetic machinery, while EI plants allocated more resources to defense. Thus EI plants were superior to EF plants in terms of nutrient conservation. In the drought unfertilized treatment, no significant difference occurred between EI and EF plants. Our results support the idea that the endophyte-grass interactions are dependent on available resources. However, we did not find a clear cost of endophyte infection. For A. sibiricum, fertilizer addition resulted in greater benefits of the symbiosis for plant growth, but this advantage decreased under drought.